PENGARUH PEMBERIAN EKSTRAK ETANOLIK KELOPAK BUNGA ROSELLA (Hibiscus sabdariffa Linn.) TERHADAP KADAR High Density Lipoprotein (HDL) PADA TIKUS PUTIH JANTAN GALUR WISTAR HIPERLIPIDEMIA - Maria Ulfah; Aristha Puji Wahyuningrum (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2010)
ABSTRACT Empirical experience-based, Rosella (Hibiscus sabdariffa linn) have a special efficacy as anticholesterol. The objectives of this research were to find out whether the effect of ethanolic extracts of rosella flowers, have an effect in increasing HDL cholesterol levels in male rats of wistar strain of hyperlipidemia and to discovering of increased HDL cholesterol effect from the extract on the experiment. This experimental research used 30 male wistar strain white mice divided into 5 groups. The negative control group was feed with 0.5% CMC Na solution and high-lipid meals. The positive control group was feed with 151 mg/kg BW gemfibrozil solution. The three experimental groups were feed orally with ethanol extracts of rosella flowers of 18.9 mg/kg BW, 37.8 mg/kg BW and 75.6 mg/kg BW dosages, respectively, for 14 days. The HDL levels in the subject animals were measured using Precipitation methods for the LDL, VLDL and Chylomicron. The data in the evaluation of HDL cholesterol levels after administration of test preparations and the percentage increase in HDL levels. Data obtained by the HDL cholesterol levels were analyzed by using One Way Anova test and it continued by using Tukey test. The result showed that the ethanolic extracts of rosella flowers dose 18.9 mg/kg BW (p = 0.016), 37.8 mg/kg BW (p = 0.004) and 75.6 mg/kg BW (p = 0.004) can increase levels HDL wistar strain male rats were significantly hyperlipidemia when compared with negative control group. The optimum dose of the ethanolic extract of rosella flowers which can increase HDL levels in the dose of 75.6 mg/kg BW with a percentage increase in HDL Levels of 29.87%. Key words: Hyperlipidemia, HDL, Ethanolic Extracts of Rosella Flowers